In Anita Nair’s New Women Batter than Man - Singh, Joga (Innovative Research Thoughts, 2017)
Feminism is a criticism of the prevailing social conditions, which have excluded women from the dominant male culture, social, political and intellectual pursuits. Modernity is clearly evident in the emergence of the new woman writing. The differences are notable in the pioneering work of modernist women writers. This paper effort is going to make a study of the changing roles of women in Indian society by taking into consideration Anita Nair’s The Better Man, the novelist of the Post independent era who have very skillfully and effectively presented the predicaments which are imposed upon them and while fighting against these predicaments, how they come out of their traditional roles as a mother, daughter, sister and above all as a wife or a home maker and acquire many unimagined and novel roles like teacher, social worker, social activist, businesswoman or corporate personality and many more. Most often female characters are fixed by gender stereotypes so that their attempts to transcend this position are often questioned.